Open innovation ecosystem organizing from a process view: a longitudinal study in the making of an innovation hub. (8th June 2022) - Remneland Wikhamn, Björn; Styhre, Alexander
Abstract : This paper uses process theory as a theoretical lens to analyze AstraZeneca's enactment of an open innovation initiative with the purpose of strengthening the firm's surrounding innovation ecosystem. Based on empirical data collected over 7 years, we develop a process model of open innovation enactment and explain how the initiative gradually transformed while maintaining its guiding principles, which were set from the start. In applying a process perspective, we highlight open innovation initiatives as dynamic and evolutionary – but not deterministic – developments. As such, we provide a comprehensive and more nuanced understanding of not only what open innovation is but also how it becomes . This study also contributes to the innovation ecosystem literature by theorizing how firms orchestrate innovation ecosystems through open innovation initiatives over time.